POST-COVID RECOVERY IN CHILDREN: ASSESSING MICROELEMENT IMBALANCES AND THEIR CLINICAL SIGNIFICANCE - Sharipova D.J. (Modern American Journals, 2025)
The article discusses the etiopathogenesis of COVID-19 in children, to assess the condition of post-COVID syndrome in children who have had COVID-19 depending on the severity of the infectious process.
Keywords: COVID-19, children, micronutrients, trace elements, zinc (Zn), selenium (Se), iron (Fe), copper (Cu), vitamin D, post-COVID recovery, imbalances, deficiency